Action/Leadership Logics and Action Inquiry for Personal and Organization Development with Diverse Groups - O’Loughlin, Douglas (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
This paper documents the use of frameworks and tools of Adult Development Psychology in an Organization Development Intervention (ODI). Specifically, the intervention used Action Logics and Leadership Logics as the framework for understanding adult development, and Action Inquiry as the tool for development. Harthill’s Leadership Development Profile and the Centre for Creative Leadership’s Leadership Culture Survey were used as measurements of individual and team development, respectively. The assessments showed that two of the three teams, and 14 of the 28 participants, made significant shifts in their development, and reported enhanced personal and team effectiveness. Nine other participants said that the process had been impactful for them. In addition, a number of the participants shared that they felt the process had helped them in their practice of OD. The findings of this research illustrate the applicability of Adult Developmental Psychology frameworks and tools as a methodology for personal, team, and organisation development. In light of the outcomes of this study, this method of OD could be used by those who want new ways of navigating through the fast changing and complex environments that many organizations are now facing.